Effects of Experimental Sleep Restriction on Ambulatory and Sleep Blood Pressure in Healthy Young Adults: A Randomized Crossover Study. Issue 3 (12th July 2021) - Covassin, Naima; Bukartyk, Jan; Singh, Prachi; Calvin, Andrew D.; St Louis, Erik K.; Somers, Virend K.
Abstract : Supplemental Digital Content is available in the text. Abstract : Although insufficient sleep is associated with increased cardiovascular risk, evidence of a causal relationship is lacking. We investigated the effects of prolonged sleep restriction on 24-hour ambulatory blood pressure (BP) and other cardiovascular measures in 20 healthy young participants (aged 23.4±4.8 years, 9 females), who underwent a randomized, controlled, crossover, 16-day inpatient study consisting of 4 days of acclimation, 9 days of sleep restriction (4 hours of sleep/night) or control sleep (9 hours), and 3 days of recovery. Subjects consumed a weight maintenance diet with controlled nutrient composition throughout. A 24-hour BP (primary outcome) and cardiovascular biomarkers were measured repeatedly. Polysomnographic monitoring was continuous. Comparing sleep restriction versus control sleep, 24-hour mean BP was higher (adjusted mean difference, day 12: 2.1 mm Hg [95% CI, 0.6–3.6], corrected P =0.016), endothelial function was attenuated ( P <0.001), and plasma norepinephrine increased ( P =0.011). Despite increased deep sleep, BP was elevated while asleep during sleep restriction and recovery. Post hoc analysis revealed that 24-hour BP, wakefulness, and sleep BP increased during experimental and recovery phases of sleep restriction only in women, in whom 24-hour and sleep systolic BP increased by 8.0 (5.1–10.8) and 11.3 (5.9–16.7) mm Hg, respectively (both P <0.001). Shortened sleep causes persistent elevation in 24-hour and sleep-time BP. Pressor effects are evident despite closely controlled food intake and weight, suggesting that they are primarily driven by the shortened sleep duration. BP increases are especially striking and sustained in women, possibly suggesting lack of adaptation to sleep loss and thus greater vulnerability to its adverse cardiovascular effects.